2023
DOI: 10.1093/geroni/igad061
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Relationships Between Nursing Home Staff Care Approaches and Behaviors of Residents With Dementia During Mealtimes: A Sequential Analysis

Abstract: Background and Objectives Optimal dyadic interactions are critical to quality mealtime care and outcomes. Prior work supports associative relationships between staff approaches and individual mealtime behaviors, yet evidence on temporal relationships is limited. This study examined temporal associations between staff approaches and resident behaviors during mealtimes. Research Design and Methods Videotaped mealtime observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Utterance quality in the study sample had limited variations (99.1% positive and 0.9% negative in staff utterances, 86.7% positive and 13.3% negative in resident utterances). Further analysis indicated that staff positive utterances (n = 2963) were distributed across all eight codes (see Data Coding section) with varied frequencies (ranging from 927 to 52) and were primarily coded as orientation/giving instructions (n = 927, 31.3%) which may require more words, while resident positive utterances (n = 772) were primarily showing interest (n = 294, 38.1%) and approval/agreement (n = 265, 34.3%) which may only require fewer words [ 29 ]. Future work needs to examine the role of speaker and utterance quality on expression length using more diverse samples.…”
Section: Discussionmentioning
confidence: 99%
“…Utterance quality in the study sample had limited variations (99.1% positive and 0.9% negative in staff utterances, 86.7% positive and 13.3% negative in resident utterances). Further analysis indicated that staff positive utterances (n = 2963) were distributed across all eight codes (see Data Coding section) with varied frequencies (ranging from 927 to 52) and were primarily coded as orientation/giving instructions (n = 927, 31.3%) which may require more words, while resident positive utterances (n = 772) were primarily showing interest (n = 294, 38.1%) and approval/agreement (n = 265, 34.3%) which may only require fewer words [ 29 ]. Future work needs to examine the role of speaker and utterance quality on expression length using more diverse samples.…”
Section: Discussionmentioning
confidence: 99%